The Effectiveness of the Carburizing Process on ST 42 Steel With Variations of Donor Media - Hesti Istiqlaliyah; Mohammad Ilham (Universitas Muhammadiyah Sidoarjo, 2021)
Carburizing is a process of adding carbon content in steel by using solid media. This study aims to determine the effectiveness of the carburizing process on the hardness and depth of carbon diffusion on ST 42 steel with a variety of donor media. Meanwhile, the donor media used were teak wood charcoal, coconut shell charcoal, and graphite. The results of this study are the highest level of hardness in coconut shell charcoal, namely 815.39 HV, teak charcoal 715.5 HV, and the lowest hardness is graphite at 343.975 HV. While the highest average carburizing depth was coconut shell charcoal of 0.0133 µ, teak charcoal at 0.0085 µ, and graphite by 0.00416 µ. This shows that there are differences in the hardness value and the depth of carbon diffusion in the three types of donor media used in the carburizing process, so it can be concluded that the type of donor media can also affect the effectiveness of the carburizing process itself.